Predictors for adherence in hypertensive therapy- A study in rural area of District Dehradun - Srivastava, Ashok Kumar; Kandpal, Sunil Dutt; Sati, Hemchandra (Indian Journal of Community Health, 2015)
Background: The adherence to hypertensive medication is not good in our country making it an important medical and public health issue. Factors contributing to non-compliance may vary from country to country. It is furthermore a dynamic phenomenon and its degree vary from time to time. Information on the degree of anti-hypertensive treatment compliance is lacking in our country. Objectives: (1) Measuring the medication adherence using validated tools and (2) investigating the patient related, disease related, medication related and health care system related factors affecting patients adherence to anti-hypertensive therapy. Methodology: a) Study design: cross sectional descriptive questionnaire based analytical study b) Sampling: Multistage sampling method c) Statistical analysis: Chi square, odds ratio and linear regression. Results: a) Adherence to antihypertensive therapy was 73%, b) Age was found to be significantly and independently associated with adherence, c) Patients on mono therapy were less adherent compared to those on two or three drugs, d) Patients who were aware of the association between certain risk factors for hypertension had better adherence. Conclusion: Future studies are recommended to confirm our findings, as adherence to medication predicts better outcomes and indicators of poor adherence to a medication needs counselling and interventions to improve adherence